Kepastian Hukum Mengenai Status Hukum "Rumpon" Sebagai Alat Bantu Penangkapan Ikan Dalam Peraturan Perundang - Undangan - Emiel Salim Siregar; Dea Resti Piranda (Jurnal Ilmiah Wahana Pendidikan, 2026)
The use of fishing aids in the form of FADs (Fish Aggregating Devices) in Indonesian waters has triggered legal complexities between fisheries modernization and potential conflicts over the use of marine space. Normatively, FADs are regulated in Minister of Maritime Affairs and Fisheries Regulation Number 18 of 2021. However, the legal status of FADs often triggers debate regarding private ownership rights over open access or state-controlled marine regimes. This article aims to analyze legal certainty regarding the status of FADs, permits, and the legal implications for fishing conflicts. This research uses a normative juridical method with a statutory and conceptual approach. The research results show that even though regulations have stipulated the obligation of a FAD Placement Permit (SIPR), there is still a normative fog regarding the exclusive rights to use fish around FADs which are often claimed to "belong" to the FAD installer. This triggers horizontal conflicts between fishermen. Therefore, firm enforcement of administrative and criminal laws against illegal FADs is needed as well as legal understanding that the installation of FADs does not give rise to ownership rights over water areas.